A new approach for the detection of obesity-related airway obstruction in lung-healthy individuals. (December 2022) - Jörres, Rudolf A.; Scholl, Nicola; Dressel, Holger; Kauffmann-Guerrero, Diego; Karrasch, Stefan; Ochmann, Uta; Kneidinger, Nikolaus; Alter, Peter; Magnussen, Helgo; Behr, Jürgen; Nowak, Dennis; Kahnert, Kathrin
Abstract: Background: Subjects with obesity show an increased prevalence of airway obstruction but it is not clear in each case whether this reflects genuine lung disease. Via intentional increase in end-expiratory lung volume we studied the detection of obesity-induced airway obstruction in lung-healthy obese subjects. Methods: The primary study population comprised 66 lung-healthy obese subjects and 23 normal weight subjects. Measurements were performed in a body plethysmograph allowing for recording and quantification of breathing loops in terms of specific airway resistance at both normal and intentionally elevated end-expiratory lung volume. The change in volume was documented by a shutter maneuver. Results: The voluntary increase of lung volume led to a significant reduction of expiratory airway resistance in 11 of the 66 obese subjects. This reduction could be quantified by a change of total expiratory resistance (sRtEX) of >1 kPa*s but was also clearly visible in the breathing loops. sRtEX showed the largest change among all resistance parameters. The loops of normal weight subjects remained virtually unaffected by the change in lung volume. Moreover, those of 5 obese patients with COPD who were measured for comparison partially showed a reduction of resistance but airway obstruction remained. Conclusion: The proposed breathing maneuver was simple to perform and allowed for a quantitative and qualitative detection of obesity-induced airway obstruction. This might help in reducing the likelihood of misdiagnosis and overtreatment of obese patients. Highlights: We propose a method to detect obesity-related airway obstruction via body plethysmography. This method is based on a simple breathing maneuver and directly visualizes the result. Applicability and usefulness are demonstrated in lung-healthy obese subjects. Our results are easily applicable and might help to avoid misdiagnosis and overtreatment.